Reconfigurable Antenna Assisted Intrusion Detection in Wireless Networks - Prathaban Mookiah; John M. Walsh; Rachel Greenstadt; Kapil R. Dandekar (International Journal of Distributed Sensor Networks)
Intrusion detection is a challenging problem in wireless networks due to the broadcast nature of the wireless medium. Physical layer information is increasingly used to protect these vulnerable networks. Meanwhile, reconfigurable antennas are gradually finding their way into wireless devices due to their ability to improve data throughput. In this paper, the capabilities of reconfigurable antennas are used to devise an intrusion detection scheme that operates at the physical layer. The detection problem is posed as a GLRT problem that operates on the channels corresponding to the different modes of a reconfigurable antenna. The performance of the scheme is quantified through field measurements taken in an indoor environment at the 802.11 frequency band. Based on the measured data, we study the achievable performance and the effect of the different control parameters on the performance of the intrusion detection scheme. The effect of pattern correlation between the different modes on the scheme's performance is also analyzed, based on which general guidelines on how to design the different antenna modes are provided. The results show that the proposed scheme can add an additional layer of security that can significantly alleviate many vulnerabilities and threats in current fixed wireless networks.